Penyelesaian Sengketa Hak Atas Tanah Marga Masyarakat Hukum Adat Suku Woirata Di Pulau Kisar Kabupaten Maluku Barat Daya - Ruben Lewedalu; Jenny Kristiana Matuankotta; Novyta Uktolseja (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Land disputes that occur in the Woirata tribal indigenous peoples are disputes over clan land rights for which until now there has been no attempt solution.Purposes of the Research: This study aims to examine and determine the dispute resolution mechanism according to the customary law of the Woirata tribe..Methods of the Research: This research is an empirical legal research, using a law approach and a case approach. Research data sources include primary, secondary and tertiary data sources. Data collection techniques in the form of library research and field studies. Technical Analysis of the data used is descriptive qualitative.Results of the Research: The results of the study show that the settlement of disputes over clan land rights based on the customary law of the Woirata tribe can basically be resolved in two ways, namely through the Soa-level customary institutions and the Village/State-level customary institutions. In this regard, the customary law community of the Woirata tribe usually prefers to use the customary law approach to resolve all problems that occur in the village related to civil matters, such as problems over land that occur.